Enzyme-catalyzed and binding reaction kinetics determined by titration calorimetry - Hansen, Lee D.; Transtrum, Mark K.; Quinn, Colette; Demarse, Neil (Biochimica et biophysica acta, 2016)
Isothermal calorimetry allows monitoring of reaction rates via direct measurement of the rate of heat produced by the reaction. Calorimetry is one of very few techniques that can be used to measure rates without taking a derivative of the primary data. Because heat is a universal indicator of chemical reactions, calorimetry can be used to measure kinetics in opaque solutions, suspensions, and multiple phase systems and does not require chemical labeling. The only significant limitation of calorimetry for kinetic measurements is that the time constant of the reaction must be greater than the time constant of the calorimeter which can range from a few seconds to a few minutes. Calorimetry has the unique ability to provide both kinetic and thermodynamic data. This article describes the calorimetric methodology for determining reaction kinetics and reviews examples from recent literature that demonstrate applications of titration calorimetry to determine kinetics of enzyme-catalyzed and ligand binding reactions. A complete model for the temperature dependence of enzyme activity is presented. A previous method commonly used for blank corrections in determinations of equilibrium constants and enthalpy changes for binding reactions is shown to be subject to significant systematic error. Methods for determination of the kinetics of enzyme-catalyzed reactions and for simultaneous determination of thermodynamics and kinetics of ligand binding reactions are reviewed. This article is part of a Special Issue entitled Microcalorimetry in the BioSciences — Principles and Applications, edited by Fadi Bou-Abdallah. [Display omitted] •Single and multiple injection methods for ITC kinetics are described and compared.•Calorimeter time constant correction is discussed.•Methods for solving the Michaelis–Menten and Ng kinetic equations are presented.•A model for the complete temperature dependence of enzyme-catalyzed reactions is presented.•A new method for blank correction and calculation of Kequil, ΔrH, and rate constants is developed.